The Effect of Access to Financial Assistance on the Mental Health of College Students During the Covid-19 Pandemic - Lazuardi Imani Hakam; Muhammad Hanri (Kusuma Negara Business School, 2021)
The Covid-19 pandemic situation affects the social and psychological conditions of the community, including university students. One of the pressures felt by students is psychological pressure due to decreased ability to pay tuition fees. The government's policy to ease the university students' financial burden is regulated by the Regulation of the Minister of Education and Culture (Permendikbud) No. 25 of 2020 concerning Standards of Higher Education Operational Cost Units. This study aims to determine the effect of financial assistance on students' mental health and determine the differences in mental health conditions of students who get access to financial assistance with students who do not get access to financial assistance. Quasi-experimental testing with the Difference in Difference (DiD) regression method found that students who gained financial assistance experienced a significant decrease in average psychological distress. Students who get access to financial assistance in installment schemes or deductions experience a significant average psychological pressure decrease. Therefore, access to financial assistance for college students can improve the quality of students' mental health so that financial assistance can be one solution in maintaining people's mental health when there is a shock in the economy.